2012
DOI: 10.2337/db11-0944
|View full text |Cite
|
Sign up to set email alerts
|

miR-33a Modulates ABCA1 Expression, Cholesterol Accumulation, and Insulin Secretion in Pancreatic Islets

Abstract: Changes in cellular cholesterol affect insulin secretion, and β-cell–specific deletion or loss-of-function mutations in the cholesterol efflux transporter ATP-binding cassette transporter A1 (ABCA1) result in impaired glucose tolerance and β-cell dysfunction. Upregulation of ABCA1 expression may therefore be beneficial for the maintenance of normal islet function in diabetes. Studies suggest that microRNA-33a (miR-33a) expression inversely correlates with ABCA1 expression in hepatocytes and macrophages. We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 25 publications
3
91
0
2
Order By: Relevance
“…The chronic hyperglycemia characteristic of diabetes has long been established the result of inadequate insulin action making one of the prime directives of the β-cell field to identify genes and mechanisms which contribute to reduced growth and function of this cell type. Since the first gain and loss of function studies on miR-375, several subsequent reports have identified a number of additional miRNAs as negative regulators of β-cell function including miR-7, miR-184, miR-21, miR-29a and miR-33a [5] [12] [8] [17] [18]. Importantly, the role of several miRNAs as negative regulators has been substantiated using specific genetic mouse knockouts [19].…”
Section: Microrna Profiling In the Pancreatic β-Cell And Isletsmentioning
confidence: 99%
“…The chronic hyperglycemia characteristic of diabetes has long been established the result of inadequate insulin action making one of the prime directives of the β-cell field to identify genes and mechanisms which contribute to reduced growth and function of this cell type. Since the first gain and loss of function studies on miR-375, several subsequent reports have identified a number of additional miRNAs as negative regulators of β-cell function including miR-7, miR-184, miR-21, miR-29a and miR-33a [5] [12] [8] [17] [18]. Importantly, the role of several miRNAs as negative regulators has been substantiated using specific genetic mouse knockouts [19].…”
Section: Microrna Profiling In the Pancreatic β-Cell And Isletsmentioning
confidence: 99%
“…Although the anti-miR33 LNA oligonucleotide used in this study increased HDL-C in Ldlr Ϫ / Ϫ mice on a chow diet, it also increased total plasma cholesterol and triglyceride levels ( 38 ), effects not seen in previous studies ( 34,37 ). These effects on HDL-C and total plasma cholesterol were not sustained when the mice were switched to a 1.25% cholesterol-containing Western diet, despite hepatic increases in ABCA1, and no effect on atherosclerotic plaque size was observed ( 39 ). While the reasons for the different outcome observed in this study are unknown, they may relate to the bioavailability and potency of the anti-miR-33 oligonucleotides used, the effects of oligonucleotide treatment concurrent with Western diet feeding, and the cholesterol content of the different Western diets used [1.25% ( 38 ) vs. 0.15% ( 37 )].…”
Section: Mirnas Targeting Sr-bimentioning
confidence: 58%
“…While the reasons for the different outcome observed in this study are unknown, they may relate to the bioavailability and potency of the anti-miR-33 oligonucleotides used, the effects of oligonucleotide treatment concurrent with Western diet feeding, and the cholesterol content of the different Western diets used [1.25% ( 38 ) vs. 0.15% ( 37 )]. In addition to improving arterial health, miR-33 inhibition may also be a viable strategy to treat individuals with combined defects in ␤ -cell function and plasma lipids ( 39 ), as elevated islet cholesterol impairs ␤ -cell function and glucose tolerance ( 39 ). In this setting, miR-33 inhibition in pancreatic islets increased ABCA1 expression, enhanced the removal of excess cholesterol from ␤ -cells and restored normal insulin secretion.…”
Section: Mirnas Targeting Sr-bimentioning
confidence: 99%
“…Acute cholesterol depletion rescued the exocytotic defect in beta cells lacking ABCA1, suggesting that elevated islet cholesterol accumulation directly impairs granule fusion and insulin secretion (Kruit et al 2011). Posttranscriptional suppression of ABCA1 in beta cells by adenoviral overexpression of miR33a and miR145 also led to increased cholesterol levels and to decreased glucose-stimulated insulin secretion (Kang et al 2013;Wijesekara et al 2012). This compromised insulin secretion was again rescued by cholesterol depletion.…”
Section: Beneficial Effects Of Hdl On Insulin Secretionmentioning
confidence: 99%